Investigating the impact of justice dimension and perceived value on customer satisfaction for sharing economy - KIM, Bokyeong (KDI School, 2015)
Since the sharing economy platform is only in the embryonic stage of its development, various studies need to be conducted. Amongst the previous researches, few empirical researches have yet studied the relationship between the perception of customers and their satisfaction in the context of the sharing economy. On the preferential basis, the study defines customer perception as justice dimensions and perceived values to investigate intention, satisfaction, and loyalty. The purpose of this study, therefore, is to examine the impact of procedural, interactional, and distributive justice dimensions of customers as well as their perceived values of price, trust, and experiences on satisfaction and loyalty for the sharing economy, with regards to accommodation business. This study investigated the following research questions: i) how does the awareness of sharing economy affect Justice Dimension that includes procedural justice, distributive justice, and interactional justice? ii) how does the awareness of sharing economy affect perceived values measured by price, reliability, and experience? iii) how do justice dimensions affect potential customer intention towards the sharing accommodation? iv) how do justice dimensions affect customer satisfaction towards the sharing accommodation? v) how do perceived values affect potential customer intention towards the sharing accommodation? vi) how do perceived values affect customer satisfaction towards the sharing accommodation? vii) how does the customer satisfaction affect customer loyalty in sharing accommodation? To answer the above questions, this study utilizes the quantitative method such as factor, regression, and ANOVA analyses. The results demonstrate that the justice dimension and perceived values are valid and significant for measuring customer satisfaction in sharing accommodation. Throughout the analysis, the study proves that the customer perceptions both justice dimensions and perceived values play an essential role in improving their satisfaction. The motivation of this study is based on the belief that the studies on customer satisfaction are of the primary concern in improving the sharing economy platform in the long run. The paper, therefore, provides both theoretical and managerial implications for the future analysis on the relationship between customer justice, perceived values, and their satisfaction in sharing accommodation industries.
Thesis(Master) --KDI School:Master of Development Policy,2015